IFN-γ-Primed hUCMSCs Significantly Reduced Inflammation via the Foxp3/ROR-γt/STAT3 Signaling Pathway in an Animal Model of Multiple Sclerosis - Ling, Xiao; Wang, Teng; Han, Chao; Wang, Pin; Liu, Xiaoli; Zheng, Chengyun; Bi, Jianzhong; Zhou, Xiaoyan (Frontiers in Immunology, 2022)
Our previous study showed that interferon-γ (IFN-γ) might enhance the immunosuppressive properties of mesenchymal stem cells (MSCs) by upregulating the expression of indoleamine 2, 3-dioxygenease. Therefore, we treated experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis (MS), with IFN-γ-primed human umbilical cord MSCs (IFN-γ-hUCMSCs). This study aimed to investigate the potential therapeutic effects of IFN-γ-hUCMSCs transplantation and identify the biological pathways involved in EAE mice. First, the body weight and clinical scores in EAE mice were recorded before and after treatment. Then, inflammatory cytokine levels in splenic cell supernatants were quantified by enzyme-linked immunosorbent assay. Finally, the mRNA expression levels of signal transducers and activators of transduction-3 (STAT3), retinoic acid-related orphan receptor γt (ROR-γt), and forkhead box P3 (Foxp3) were detected by quantitative reverse transcription-polymerase chain reaction. We observed that IFN-γ-hUCMSCs transplantation significantly alleviated body weight loss and decreased clinical scores in mice. Additionally, IFN-γ-hUCMSCs transplantation could regulate the production of inflammatory cytokines, interleukin (IL)-10 and IL-17, thereby showing more potent treatment efficacy than hUCMSCs transplantation (p<0.05). Compared with the EAE group, the expression of STAT3 and ROR-γt in the transplantation groups was significantly decreased, but the expression of Foxp3 was significantly upregulated, in the IFN-γ-hUCMSCs transplantation group than in the hUCMSCs transplantation group. We assumed that IFN-γ-hUCMSCs may affect the Th17/Tregs balance through the Foxp3/ROR-γt/STAT3 signaling pathway to reduce the inflammatory response, thereby improving the clinical symptoms in EAE mice. Our study demonstrated that transplantation of IFN-γ-hUCMSCs could reduce inflammation in EAE mice via the Foxp3/ROR-γt/STAT3 signaling pathway, highlighting the therapeutic effects of IFN-γ-hUCMSCs in patients with MS.